2021
DOI: 10.1002/ijgo.13696
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum retained products of conception: Is it possible to avoid postpartum curettage?

Abstract: Retained products of conception (RPOC) occur in up to 1% of deliveries. 1 Although uncommon, surgical procedures for removal of RPOC may be required in these parturients, associated with the long-term sequelae of intrauterine adhesions, abnormal placentation, and infertility. 2,3 Consequently, Asherman's syndrome following postpartum surgical procedures for removal of RPOC has emerged as a major cause for litigation. 4 With the aim of optimizing the postpartum management of women considered at risk for RPOC wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…It can be seen that there are many risk factors leading to intrauterine adhesions. The results of meta-analysis of this study showed that pelvic inflammation (OR = 2.05, 95% CI: 1.24~3.38, p = 0.005), negative pressure during uterine suction (OR = 125.61, 95% CI: 67.35~183.87, p < 0.0001) and uterine suction time (OR = 4.52, 95% CI: 4.21~4.84, p < 0.00001) were the risk factors leading to intrauterine adhesions, which were supported by previous studies [ 25 27 ]. However, the number of pregnancies (OR = 0.47, 95% CI: -0.35~1.29, p = 0.26), the number of curettages (OR = 0.48, 95% CI: -0.63~1.60, p = 0.40), the average number of births (OR = 0.44, 95% CI:-0.14~1.02, p = 0.14), abortion (OR = 1.08, 95% CI: 0.63~1.85, p = 0.77), myomectomy (OR = 1.35, 95% CI: 0.39~4.67, p = 0.63), menstrual abnormalities (OR = 0.83, 95% CI: 0.09~7.36, p = 0.87), and infertility (OR = 0.51, 95% CI: 0.06~4.00, p = 0.52) had little impact on the occurrence of intrauterine adhesions.…”
Section: Discussionsupporting
confidence: 84%
“…It can be seen that there are many risk factors leading to intrauterine adhesions. The results of meta-analysis of this study showed that pelvic inflammation (OR = 2.05, 95% CI: 1.24~3.38, p = 0.005), negative pressure during uterine suction (OR = 125.61, 95% CI: 67.35~183.87, p < 0.0001) and uterine suction time (OR = 4.52, 95% CI: 4.21~4.84, p < 0.00001) were the risk factors leading to intrauterine adhesions, which were supported by previous studies [ 25 27 ]. However, the number of pregnancies (OR = 0.47, 95% CI: -0.35~1.29, p = 0.26), the number of curettages (OR = 0.48, 95% CI: -0.63~1.60, p = 0.40), the average number of births (OR = 0.44, 95% CI:-0.14~1.02, p = 0.14), abortion (OR = 1.08, 95% CI: 0.63~1.85, p = 0.77), myomectomy (OR = 1.35, 95% CI: 0.39~4.67, p = 0.63), menstrual abnormalities (OR = 0.83, 95% CI: 0.09~7.36, p = 0.87), and infertility (OR = 0.51, 95% CI: 0.06~4.00, p = 0.52) had little impact on the occurrence of intrauterine adhesions.…”
Section: Discussionsupporting
confidence: 84%
“…Currently, the diagnosis is based on the combination of clinical findings and US evaluation (which includes gray-scale and Doppler flow scans), and the management is preferably by hysteroscopy, with low rates of postoperative IUAs and high rates of subsequent fertility (Capmas et al, 2019;Smorgick et al, 2014;Hooker et al, 2016). Indeed, a recent study comparing the management of postpartum RPOC between two periods has showed that most cases of RPOC are currently managed by hysteroscopy rather than curettage and that the rates of postoperative IUAs have concurrently decreased (Nir et al, 2022). Furthermore, thanks to the availability of HTRS and the miniresectoscope, many hysteroscopic procedure can now be performed without anaesthesia or cervical dilation in an ambulatory setting.…”
Section: Discussionmentioning
confidence: 99%